Molecular assessment of NMDAR subunits and neuronal apoptosis in the trigeminal ganglion in a model of male migraine-induced rats following Moringa oleifera alcoholic extract administration - Ahmad Vafaeian; Ali Vafaei; Mohammad Reza Parvizi; Mohsen Chamanara; Mojgan Mehriardestani; Yasaman Hosseini (BMC Neuroscience)
Abstract Introduction Migraine, a common disorder marked by severe and repetitive headaches, has been linked to the involvement of the NMDA receptor (NMDAR), a receptor responsible for glutamate signaling. Moringa oleifera (M. oleifera), recognized for its anti-inflammatory properties and therapeutic potential in various conditions, has been investigated. This study aims to assess the efficacy and precise mechanisms of M. oleifera for the treatment of migraine, for which evidence is limited. Methods Rats were stratified into four distinct groups. The control group did not undergo the migraine-induction protocol. Post-induction, the “sumatriptan” group was administered sumatriptan injections, the “treatment” group received oral M. oleifera extract, and the “vehicle” group was provided with oral solvent treatment. Behavioral evaluations encompassing Von Frey’s and hot plate assessments, in addition to qPCR analysis targeting Nr2a, Nr2b, Bax, Bcl-2, and Caspase-3, were conducted. Results Von Fery’s and hot plate tests revealed a notable decrease in triggering pressure and temperature within the vehicle group when compared to the other groups (both ps < 0.001). The Nr2a expression levels in both the vehicle and treatment cohorts exhibited significantly higher values than those observed in the control group (p < 0.001, p = 0.001) and the sumatriptan group (p < 0.001, p = 0.002). Conversely, no substantial alterations in Nr2b or Bcl-2 expression levels were observed across the study groups (p = 0.404, p = 0.976). Notably, heightened expressions of Caspase-3 and Bax were evident in the vehicle group relative to the other groups (p = 0.013, p = 0.010). Conclusions Moringa oleifera extract appears to mitigate symptoms of migraine by inhibiting apoptosis, suggesting potential efficacy in migraine treatment; however, additional research investigating a wider range of pathways is necessary. Clinical trial number Not applicable.